2019
DOI: 10.1088/1757-899x/532/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Single stage dimethyl ether plant model based on gasification of palm empty fruit bunch

Abstract: Biomass from empty fruit bunch (EFB) is considered as potential renewable energy sources to be developed in Indonesia. EFB can be efficiently converted into valuable and useful fuel products through gasification. Gasification is a process of biomass conversion into syngas. Syngas is a raw material for most other chemical products, such as Methanol, Ammonia, and DME. One of the biomasses that has big potential to be utilized is palm EFB waste. Research about DME synthesis from various biomass has been done, tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…As received, OPEFB collected has 60% moisture content, and with a dry ash-free (daf) base, the feedstock rate becomes 383 t day -1 or 16 t h -1 . According to Heryadi et al [31], 1 t DME was produced for every 2 t OPEFB feedstock daf base. This ratio is applied to OPEFB biomass production, where 192 t day -1 of DME is made from 383 t day -1 OPEFB daf base input.…”
Section: Opefb Potential and Production Scenariomentioning
confidence: 99%
“…As received, OPEFB collected has 60% moisture content, and with a dry ash-free (daf) base, the feedstock rate becomes 383 t day -1 or 16 t h -1 . According to Heryadi et al [31], 1 t DME was produced for every 2 t OPEFB feedstock daf base. This ratio is applied to OPEFB biomass production, where 192 t day -1 of DME is made from 383 t day -1 OPEFB daf base input.…”
Section: Opefb Potential and Production Scenariomentioning
confidence: 99%
“…Several previous studies on the conversion of OPEFB into bio-DME have reportedly been carried out since 2017. These were often related to parametric studies, which used simulation software and techno-economic analysis [3,41,55]. However, studies concerning the direct experiments on the pilot and actual plants were not found during the selection of related literature.…”
Section: Bio-dme From Opefbmentioning
confidence: 99%
“…Heryadi et al [41] described the simulation process of bio-DME conversion. This was conducted using the Aspen Hysys simulator software and the operating condition data obtained from previous literature, and examined the process of DME synthesis.…”
Section: Bio-dme From Opefbmentioning
confidence: 99%
“…Optimizing the use of rice husk as a renewable energy source through the thermochemical process (pyrolysis or gasification) is still an attractive alternative in future energy supplies. The process converts rice husks into gas and/or liquid that can be utilized directly as energy or a feedstock to produce valuable chemicals (Wang et al, 2018;Salman et al, 2018;Heryadi et al, 2019). Researchers have performed studies to ensure that the pyrolysis or gasification process produces more gas with low tar and high CO and H2 contents.…”
Section: Introductionmentioning
confidence: 99%